Complete mitochondrial genome of Polyphaga plancyi (Blattaria: Polyphagidae). Issue 1 (1st January 2016) - Liu, Gang; Liu, Mengwei; Hui, Wenyu; Chen, Chuanqin; Zhang, Yingyin
Abstract: The complete mitochondrial genome of Polyphaga plancyi is a 15, 547 bp circular molecule, which contains 37 typical mitochondrial genes (13 protein-coding genes, 2 rRNAs and 22 tRNAs) and a 854 bp D-loop. Its gene arrangement pattern is identical with typical other cockroaches. All protein-coding genes start with an ATG codon except COI, ND3, ND5, ND4, ND4L ND6 and ND1. TAA is the most frequent stop codon, and TAG, GCA, TA- and T- are also occurred very common. The mtDNA sequence contains 12S rRNA and 16S rRNA of rRNA. Except for tRNA Ser(AGY) and tRNA Leu(CUN) without the dihydrouridine (DHU) arm, all tRNAs could be folded into canonical cloverleaf secondary structures. The phylogenetic trees from the ML and BI analyses based on the complete mtDNA of nine cockroaches' species, share similar topologies and high node support values. Polyphaga plancy has close relative with Eupolyphaga sinensis .